MODEL BIMBINGAN KELOMPOK SEBAGAI STRATEGI PENDIDIKAN KARAKTER BERBASIS LATIHAN PERMAINAN - DARIMIS DARIMIS (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2014)
The reality of students’ negative attitude made Indonesia goverment had not moved forward nowadays. Most people judged that educational system should take the responsibility to this condition. Education was assumed laying on students’ cognitive rather than affective and conative. Reliazing this phenomena, counceling as a part of education offered group counceling as one strategy of character education based playing games. There were twelve playing games that could be applied to build positive character: the practice writing, body movement, circleling, dyad, triad, creative group, art and handcraft, fantasy, reading, feedback, belief, moral dilemma, and group decision. Kata kunci: bimbingan kelompok, karakter, dan latihan permainan